The development of a virtual simulator for a novel design surgical tool in endoscopic endonasal transsphenoidal surgery - Nantida Nillahoot; Branesh M. Pillai; Sorayouth Chumnanvej; Jackrit Suthakorn (Institute of Advanced Engineering and Science, 2021)
Endoscopic endonasal transsphenoidal surgery (EETS) is a standard procedure to treat the pituitary adenoma, a tumor in the pituitary gland that causes malfunction of hormones. Although the method is substantially minimal invasive, the surgeon may encounter intricacies. The major challenges are narrow surgery pathway, limited working area, lack of case studies for practicing, steep learning curve owing to the intricate steps, and the tool insertion risk. To ease the neurosurgeons, this research focuses on the development and testing of the surgical simulator based on the pathway guidance and the interchangeable surgical instrument tooltip. The system was tested in human cadaver-based experiments with interchangeability in terms of function and the performance of the simulator in terms of the benefits. The experiments demonstrate the augmentation in the learning skill of the user through the simulator based on the completion time assessment and the error reduction. Furthermore, the satisfaction level of the interchangeable surgical tool, which was found using sliding switch and gripper scored 71.40%, the interchangeable tooltip function, which is a novel function to participants scored 85.6% and the practical use had 77%. The geometric aspect of the interchangeable tool scored lowest (62.80%) and was found to be moderate among the neurosurgeons.